Race, Crime, and the Public's Sentencing Preferences. (30th June 2022) - Doherty, David; Dowling, Conor M; Miller, Michael G; Tuma, Michelle D
Abstract: We report findings from a conjoint experiment where respondents indicated what they viewed as an appropriate sentence for a series of hypothetical individuals convicted of federal crimes. The experiment signaled the race of the defendant by using distinctively "Black" and "white" names, allowing us to assess whether Americans are more punitive toward purportedly Black defendants. We also consider whether signals of the defendant's race condition the effects of the crime and various defendant characteristics. Surprisingly, the direct effect of our signal of defendants' purported race is null. We present evidence that this null finding is a product of offsetting tendencies: respondents who view persistent racial inequalities as the product of both past and ongoing institutional factors prescribed lengthier sentences for white defendants; those who discount these explanations prescribed lengthier sentences for Black defendants. 1 We find only scattered evidence that the signal of defendants' race moderates the effects of other characteristics of the crime and defendant. Our approach and findings not only offer insights into how racial attitudes shape perceptions regarding what constitutes just punishment for crimes in the contemporary United States, but also demonstrate a novel approach to studying this domain and point to an array of promising avenues for future research.